Myricitrin inhibits fibroblast-like synoviocyte-mediated rheumatoid synovial inflammation and joint destruction by targeting AIM2 - Shen, Chuyu; Xu, Meilin; Xu, Siqi; Zhang, Shuoyang; Lin, Wei; Li, Hao; Zeng, Shan; Qiu, Qian; Liang, Liuqin; Xiao, Youjun; Xu, Hanshi (Frontiers in Pharmacology, 2022)
Objective. To explore the effect and underlying mechanism of Myricitrin (Myr) in regulating fibroblast-like synoviocyte (FLS)-mediated synovitis and joint destruction in RA. Methods. FLSs were isolated from synovial tissues from patients with RA. Gene expression was measured using quantitative RT-qPCR. Protein expression was detected by immunohistochemistry or Western blot. Cell apoptosis was performed by an Annexin-PI staining assay. EdU incorporation was used to assess the proliferation of RA FLS. Transwell assay was used to characterize the cell migration and invasion ability of RA FLS. The potential target of Myr was identified by RNA sequencing analysis. The in vivo effect of Myr was assessed in a collagen-induced arthritis (CIA) model. Results. Myr treatment inhibited the lamellipodia formation, migration, and invasion, but not the apoptosis and proliferation, of RA FLSs. Myr also reduced the expression of CCL-2, IL-6, IL-8, MMP-1, MMP-3, and MMP-13 induced by TNF-α. The RNA-seq results indicated that AIM2 may be a target gene of Myr in RA FLSs. Furthermore, compared to healthy controls, AIM2 expression showed higher levels in synovial tissues and FLSs from RA patients. AIM2 knockdown also inhibited RA FLS migration, invasion, cytokine, and MMP expression. In addition, either Myr treatment or AIM2 knockdown reduced the phosphorylation of AKT induced by TNF-α stimulation. Importantly, Myr administration relieved arthritis symptoms and inhibited AIM2 expression in the synovium of CIA mice. Conclusion. Our results indicate that Myr exerts an anti-inflammatory and anti-invasion effect in RA FLSs and provide evidence of the therapeutic potential of Myr for RA.